Empresas de copropriedade dos empregados alcançam desempenho superior? - Monetti, Fabiano (2024)
Most empirical studies have observed a positive, though weak, correlation between employee ownership and firm performance. The incorporation of mediators and moderators has not significantly expanded our understanding of the topic. Scholars have come to conclusion that such a relationship is undertheorized and more complex than most existing studies have assumed. I argue that the prevalent theoretical premise, which assumes that employee ownership affects firm performance mainly through positive changes in employee attitudes and behaviors, does not apply in all cases. When employee ownership constitutes effective and enough property and control rights to alter labor and power relations in the company, in certain cases, a particular organizational configuration, characterized by employee (co)ownership, emerges. This research investigates whether such an organizational configuration constitutes a sufficient condition for superior firm performance. By proposing an alternative conceptual and analytical framework, based on alternative theoretical premises, configurational approach and Qualitative Comparative Analysis, I develop a more complex and nuanced theoretical explanation of the conditions that relate employee ownership and firm performance, I empirically confirm the research hypothesis, and I demonstrate that employee ownership, as the constitutive core of an employee co-ownership organizational configuration, has a clearer and more robust relationship with firm performance than previously observed by the field's empirical corpus. In addition to its practical implications, this research contributes to rearticulate management studies with broader social phenomena and to resume the link between participation in organizations and the political debate about alternative organizational systems.